2015
DOI: 10.2174/1874110x01509012332
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Influencing Factors of Knowledge Sharing in Virtual Learning Community

Abstract: Increasing organizations and educational institutions have implemented virtual learning communities to encourage knowledge sharing. Virtual Learning Community was able to serve the learning goals of community members by relying on the knowledge sharing. In this paper, some individual factors and environmental factors were used to study the knowledge sharing among community members. In virtual learning community, the sense of community and trust are important indicators for the development of community, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The proposed framework presumes that verbal persuasion builds self-efficacy when a respective environment is encouraging and praising individuals with feedbacks for their competence to improve their effectiveness. Empirical evidence behind this proposition is found in a series of studies taken up in this document analysis like Wang and Wu (2008), Chu (2010), Wang et al (2013), Chiu and Tsai (2014), Tang et al (2014), Jan (2015), Lin et al (2015), Shen (2015), Liou et al (2016) and Hong et al (2017), etc. Positive self-talks, informal communications, human relationships, etc.…”
Section: Rq2 Factors Influencing Self-efficacy In Online Educationmentioning
confidence: 71%
See 4 more Smart Citations
“…The proposed framework presumes that verbal persuasion builds self-efficacy when a respective environment is encouraging and praising individuals with feedbacks for their competence to improve their effectiveness. Empirical evidence behind this proposition is found in a series of studies taken up in this document analysis like Wang and Wu (2008), Chu (2010), Wang et al (2013), Chiu and Tsai (2014), Tang et al (2014), Jan (2015), Lin et al (2015), Shen (2015), Liou et al (2016) and Hong et al (2017), etc. Positive self-talks, informal communications, human relationships, etc.…”
Section: Rq2 Factors Influencing Self-efficacy In Online Educationmentioning
confidence: 71%
“…The studies (e.g. Lim et al, 2016;Shen, 2015;Kuo et al, 2014;Chiu and Tsai, 2014;Joo et al, 2013;Zhang et al, 2012;Chu, 2010;Song et al, 2011) also found almost in the same tune that self-efficacy has a deep impact on the participants' personal innovativeness, communication climate, holding strong perception toward online infrastructure, motivation, asynchronous communication, learner-learner communication or learner-teachers' communication and knowledge sharing in online mode. Hence, policies to strengthen self-efficacy of the participants could prove effective in the Asian online education context.…”
Section: Self-efficacy In Online Educationmentioning
confidence: 74%
See 3 more Smart Citations